Validity of PBL E-Modules Integrated with Local Wisdom in Improving Students' Literacy and Science Process Skills - Zainuri, Baiq Nabila Saufika; Gunawan, Gunawan; Kosim, Kosim; Harjono, Ahmad; Rahayu, Satutik (Department of Physics Education, Universitas Mataram, 2025)
This study aims to develop and evaluate the validity of e-modules based on problem-based learning (PBL) integrated with local wisdom to improve students' science literacy and science process skills. The e-module was developed using the 4D development model (define, design, develop, disseminate). Validation of the e-module involved three experts by assessing aspects of content, presentation, and language and was tested using Aiken's V analysis. The validation results showed that the e-module had a high level of validity with the category “very valid,” in the aspects of content, presentation and language. In addition, the results of the validation of learning tools such as the flow of learning objectives, teaching modules, and test instruments for science literacy and science process skills also produced good assessments. These results indicate that this PBL-based e-module is not only valid for use in learning, but also effective in supporting the improvement of understanding of science concepts, appreciation of local culture, as well as science literacy and science process skills of students. Thus, this e-module has the potential to be an innovative solution for science learning that is contextual, interactive, and relevant to the needs of the 21st century.